iPSCs : state of the science - Birbrair, Alexander (Advances in stem cell biology, 2022)
"[A]ddresses the progress in induced pluripotent stem cell technologies. Somatic cells can be reprogrammed into induced pluripotent stem cells (iPSCs) by the expression of specific transcription factors. These cells are transforming biomedical research in the last 15 years. The volume teaches readers about current advances in the field. This book describes different technologies and strategies to use induced pluripotent stem cells for biological and clinical benefit. In recent years, remarkable progress has been made in the obtention of induced pluripotent stem cells and their differentiation into several cell types, tissues, and organs using state-of-art techniques. These advantages facilitated identification of key targets and definition of the molecular basis of several disorders. The volume is written for researchers and scientists interested in stem cell therapy, cell biology, regenerative medicine, and organ transplantation; and is contributed by world-renowned authors in the field"--Page 4 of cover.